Why Political Parties Colonize the Media in Indonesia: An Exploration of Mediatization - Muhammad Thaufan Arifuddin (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2016)
Mediatization has become more relevant in exploring relations between media and politics in post-Suharto Indonesia. However, the media's roles as the fourth estate of democracy has been hijacked by wealthy politicians and political parties. As a result, most mainstream media have failed to enhance public dabates democratically. Based on existing mediatization literature, politico-economy analysis, and data collected through extensive in-depth interviews and relevant documents in the 2013-2015 period, this article theoretically aims to develop the mediatization concept and explore the degree of mediatization of politics in contemporary Indonesia.